2020
DOI: 10.4314/tjpr.v19i2.14
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, antimicrobial and cytotoxicity screening of ethanol extract of <i>Acacia ehrenbergiana</i> Hayne grown in Jazan Region of Saudi Arabia

Abstract: Purpose: To explore the phytoconstituents of Acacia ehrenbergiana Hayne as well as its biological effects. Methods: Determination of phytoconstituents of ethanol extract of the plant was performed by gas chromatography-mass spectrometry (GC-MS) technique. Antibacterial screening was conducted against the isolates of Gram-positive and Gram-negative microbes while the anti-carcinogenic properties of the ethanol extract on cancerous cells were investigated by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetraz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…The free radical scavenging activity of the investigated extracts was assessed using the direct DPPH assay [ 16 ]. In this assay, DPPH (deep purple colored free radical) turns into pale yellow when reduced by antioxidants present in the sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The free radical scavenging activity of the investigated extracts was assessed using the direct DPPH assay [ 16 ]. In this assay, DPPH (deep purple colored free radical) turns into pale yellow when reduced by antioxidants present in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…A study on the ethanolic extract of Acacia ehrenbergiana showed a significant anti-inflammatory effect at a 300 mg/kg dose [ 15 ]. Another study conducted on the ethanol extract of the flower of Acacia ehrenbergiana identified 15 phytoconstituents with potent antibacterial activity against several bacterial strains including S. aureus, E. fecalis, E. coli, P. mirabilis, P. aeruginosa, and K. pneumonia [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…With continued research, these and other Saudi Arabian plants may prove to be valuable sources of natural compounds for the development of new cancer therapies. Recent studies reported that local plant extracts from Saudi Arabia, including O. heteracanthum ( Gouda et al, 2014 ), A. ehrenbergiana ( Makeen et al, 2020 ), O. vaillantii ( Gouda et al, 2014 ), C. rotundus ( AlQathama et al, 2022 ), C. carandas ( Alshehri, 2020 ), C. spinarum ( AlQathama et al, 2022 ), and C. sinensis ( Dou et al, 2021 ), exhibited remarkable and potent cytotoxic effects on the ovary cancer cell line. Nevertheless, the specific mechanisms of action underlying these medicinal plants remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The indigenous uses and pharmacological activity of these plants in Saudi Arabia demonstrate the strong relationship between local remedies, diet, health, and traditional healing practices unique to their cultures. Previous studies provide shreds of evidence that indigenous plants in Saudi Arabia, including Onopordum heteracanthum ( Gouda et al, 2014 ), Acacia ehrenbergiana ( Makeen et al, 2020 ), Osteospermum vaillantii ( Gouda et al, 2014 ), Cyperus rotundus ( AlQathama et al, 2022 ), Carissa carandas ( Alshehri, 2020 ), Carissa spinarum ( AlQathama et al, 2022 ), and Camellia sinensis ( Dou et al, 2021 ), have anti-cancer properties for ovarian cancer. Plants found in these regions have been used by local inhabitants for treating a wide range of ailments.…”
Section: Introductionmentioning
confidence: 99%
“…The clonogenic survival is a viability assay, in which the ability of individual cancer cells to form progeny colonies, was assessed based on a previous report [ 52 ]. Briefly, MCF7 cells were seeded in 2 mL of media at low density (2 × 10 2 ) in 6-well plates as duplicates.…”
Section: Methodsmentioning
confidence: 99%